Visceral fat and insulin resistance - what we know? - Janochova, Karolina; Haluzik, Michal; Buzga, Marek (Biomedical papers, 2019)
One of the most significant challenges of current medicine is the increasing prevalence of obesity worldwide that is accompanied by a wide range of chronic health complications and increased mortality. White adipose tissue actively contributes to metabolic regulation by production of a variety of hormones and cytokines, commonly referred to as adipokines. The spectrum and quantity of adipokines produced by the adipose tissue of obese patients is directly or indirectly involved in much obesity-related pathology (type 2 diabetes mellitus, cardiovascular disease, inflammatory response). One of the underlying mechanisms linking obesity, diabetes, and cardiovascular complications is subclinical inflammation, primarily arising in visceral adipose tissue. Adipocyte size, number and polarization of lymphocytes and infiltrated macrophages are closely related to metabolic and obesity-related diseases. The storage capacity of hypertrophic adipocytes in obese patients is limited. This results in chronic energy overload and leads to increased apoptosis of adipocytes that in turn stimulates the infiltration of visceral adipose tissue by immune cells, in particular macrophages. These cells produce many proinflammatory factors; while the overall production of anti-inflammatory cytokines and adipokines is decreased. The constant release of proinflammatory factors into the circulation then contributes to a subclinical systemic inflammation, which is directly linked to the metabolic and cardiovascular complications of obesity.
Keywords: adipose tissue; inflammation; insulin resistance; macrophages; obesity